Determination of energy efficiency barriers taxonomy in socio-economic model of Ukraine - Bilous, Liliia (Technology audit and production reserves, 2020)
The object of research is Ukraine socio-economic model in terms of energy efficiency factors. One of the most problematic places is the identification of energy efficiency barriers, its minimization. The process of introduction of energy efficient technologies associated with the complexity and duration of market promotion, and their relatively high cost, and is hampered by a number of obstacles, barriers to energy efficiency. An analysis of current state of Ukrainian socio-economic system is carried out. The main characteristics of barriers to energy efficiency of socio-technical system in relation to those already identified in foreign systems are identified, a new group of barriers to the gap of energy efficiency is identified. The introduction of taxonomy of energy efficiency barriers, their identification in each individual project implementation of energy efficient technologies improves their promotion and increases the economic effect of these technologies. Abstract-logistical and comparative-statistical analysis are used to study the theory and practice of energy barriers in the world and in Ukraine, as well as to identify prospects for overcoming barriers. A set of criteria that form energy efficiency barriers for Ukraine has been identified. These steps involve conducting a system-structural analysis to determine the presence of energy efficiency barriers, as well as to describe their manifestation. In addition, those barriers that exist in the socio-economic model of the country but are not described in the basic theory have been structured and described. To implement these stages, the basic structure of energy efficiency barriers was adapted to the Ukrainian socio-economic model, and a group of barriers specific to Ukraine was derived. Due to this, the terminology «taxonomy of energy efficiency barriers» was introduced into the Ukrainian scientific literature and the concept of business turnover, which was previously used only by foreign scientists.